2015
DOI: 10.1681/asn.2013090990
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hypoxia-Inducible Factors Prevents Diabetic Nephropathy

Abstract: Hyperglycemia results in increased oxygen consumption and decreased oxygen tension in the kidney. We tested the hypothesis that activation of hypoxia-inducible factors (HIFs) protects against diabetes-induced alterations in oxygen metabolism and kidney function. Experimental groups consisted of control and streptozotocin-induced diabetic rats treated with or without chronic cobalt chloride to activate HIFs. We elucidated the involvement of oxidative stress by studying the effects of acute administration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(154 citation statements)
references
References 43 publications
5
148
1
Order By: Relevance
“…A role for HIF-1 in the pathogenesis of renal fibrosis including that of diabetic nephropathy has been shown by several groups (18,38,39), although others have recently suggested that HIF activation may protect against diabetic nephropathy (40). In this latter study, diabetic rats were treated for 4 weeks with cobalt chloride, a relatively nonspecific activator of HIF.…”
Section: Discussionmentioning
confidence: 89%
“…A role for HIF-1 in the pathogenesis of renal fibrosis including that of diabetic nephropathy has been shown by several groups (18,38,39), although others have recently suggested that HIF activation may protect against diabetic nephropathy (40). In this latter study, diabetic rats were treated for 4 weeks with cobalt chloride, a relatively nonspecific activator of HIF.…”
Section: Discussionmentioning
confidence: 89%
“…This concept has been supported by numerous studies using several animal models of CKD [86][87][88]. Recently, Palm and colleagues [89] demonstrated that the administration of cobalt ameliorated kidney damage in streptozotocin-induced diabetic rats, which was accompanied by increased oxygen tension in the kidney. However, these studies have several limitations.…”
Section: Hif Stabilization As a Treatment Of Ckdmentioning
confidence: 90%
“…Several issues remain, however. In some studies, HIF-1a activation protected against kidney injury (66), suggesting that HIF-1a may not be the sole, or the best, therapeutic target for reversing cellular effects of hypoxia in CKD.…”
Section: Role Of Cellular Energy Oxygen and Nutrient Sensorsmentioning
confidence: 99%